PENGARUH PERSONAL SELLING, SALES PROMOTION DAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN PADA PT SUPERINDO KARYA GEMILANG BATAM - lymm, meilissa; Saputra, Asron (SCIENTIA JOURNAL, 2021)
This study is intended to analyze the effects of Personal selling, Sales promotion, and Distribution on consumer decisions at PT Superindo Karya Gemilang Batam. This study is categorized as quantitative research. The data were attained by distributing questionnaires. The samples comprised 115 and were attained by applying the Slovin technique. In other words, there were 115 respondents instructed to answer the questionnaires. This study utilized a non-probability technique, in which it emerged as a sampling technique that did not offer the same opportunity for every member of the population that was chosen as the sample. Additionally, the gathered data were analyzed by utilizing multiple regression analysis assisted by SPSS, version 26. The results of this study demonstrate that Personal selling (X1), Sales promotion (X2) and Distribution (X3) positively affect consumer decisions (Y). Personal selling (X1) partially gives positive and significant effects on consumer decisions (Y), and the Sales promotion (X2) partially gives positive and significant effects on consumer decisions (Y). Simultaneously, Personal selling (X1), Sales promotion (X2) and Distribution (X3) give positive and significant effects on consumer decisions (Y) at PT Superindo Karya Gemilang Batam.